Implementation fidelity of Ethiopia’s Malaria test-and-treat guideline amid a resurgence in Amhara Region: A mixed-methods study - Mastewal Worku Lake; Kassahun Alemu Gelaye; Mulusew Andualem Asemahagn; Kindie Fentahun Muchie; Hailemariam Awoke Engedaw; Muluken Azage Yenesew (PLoS ONE, 2026)
Background Ethiopia has experienced a marked malaria resurgence in recent years, with the Amhara Region disproportionately affected. Although Ethiopia’s national strategy emphasizes test-before-treat and a public–private mix, implementation fidelity of the malaria test-and-treat guideline during resurgence has not been well characterized. This study assessed fidelity to malaria diagnosis and treatment guidelines in public and private health facilities in the Amhara Region within this resurgence context. Methods We conducted a convergent parallel mixed-methods study from February to March 2025 in 53 health facilities (38 public, 15 private) in Amhara Region. The facility was the unit of analysis; one provider primarily responsible for malaria case management was interviewed per facility (n = 53). Implementation fidelity was operationalized using Carroll’s framework across three domains: content (adherence to key diagnostic/treatment steps), coverage (proportion of suspected cases tested before treatment, extracted from facility registers), and frequency (self-reported consistency of testing for febrile patients in the preceding month). Domain scores were standardized to 0–100 and averaged with equal weights to form a composite fidelity score; ≥ 75% indicated high fidelity. To explain quantitative patterns, we conducted 32 in-depth interviews and analyzed data using inductive thematic analysis with CFIR-informed interpretation. Quantitative analysis used nonparametric tests and parsimonious multivariable linear regression, with prespecified sensitivity analyses excluding the self-reported frequency domain. Results Overall mean implementation fidelity was 64.3% (SD 12.1); 40% of facilities had high fidelity (≥75%), and 13% scored <50%. Public facilities had higher fidelity than private facilities (median 67% [IQR 60–77] vs 63% [IQR 56–70]; Wilcoxon rank-sum p = 0.041). In multivariable analysis, higher fidelity was associated with higher participant responsiveness (β = 3.4, p < 0.001), stronger facilitation strategies (β = 2.8, p < 0.001), and lower perceived intervention complexity (reverse-coded; β = 2.1, p < 0.001). Interviews indicated that fidelity gaps were driven by diagnostic and treatment deviations (including non–species-specific prescribing), inconsistent counseling and follow-up mechanisms, supply constraints, and patient pressure, with challenges more frequently emphasized in private facilities. Conclusions Implementation fidelity to Ethiopia’s malaria test-and-treat guideline in Amhara during resurgence was moderate, with lower fidelity in private facilities. Provider responsiveness, facilitation strategies, and lower intervention complexity were identified as factors associated with implementation fidelity. Strengthening supportive supervision and mentorship with explicit inclusion of private facilities, improving supply reliability, and simplifying decision supports may improve adherence during resurgence.